Penerapan Model Prototipe pada Sistem Penjualan Bumbu dan Rempah Berbasis Web - Maieka Sari Istiqomah; Sumardiono Sumardiono; Agus Riyanto; Bambang Kriswantara (Universitas Informatika dan Bisnis Indonesia, 2025)
The rapid development of information technology makes technology an important asset in the advancement of sales and business systems. To compete with competitors, organizations need to implement strategies that are aligned with their vision and mission. However, UD EKA SARI handles the problem that the sales data processing process is still done manually, consumers have to come directly to the place to make product purchases and cash payment transactions, this makes the process of recapping purchase reports from suppliers and sales to consumers difficult in making reports, this is because you have to recap all transactions that occurred during the reporting period you want to make. To promote its products, it is currently carrying out marketing promotions by conducting promotional media via social media. Therefore, the author proposes to design a spice and spice sales system based on a website model prototype. Based on the results obtained from beta testing the website-based spice and spice sales system at UD Eka Sari, the percentage reached 86.7%, which states that the sales system is very good to use.